2011
DOI: 10.1186/1471-2229-11-137
|View full text |Cite
|
Sign up to set email alerts
|

Is the basal area of maize internodes involved in borer resistance?

Abstract: BackgroundTo elucidate the role of the length of the internode basal ring (LIBR) in resistance to the Mediterranean corn borer (MCB), we carried out a divergent selection program to modify the LIBR using two maize synthetic varieties (EPS20 and EPS21), each with a different genetic background. We investigated the biochemical mechanisms underlying the relationship between the LIBR and borer resistance. Selection to lengthen or shorten the LIBR was achieved for each synthetic variety. The resulting plants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
1
11
1
Order By: Relevance
“…Barros-Rios and coworkers (2011) found that the stem tunneling by ECB and MCB was negatively correlated with total DFAs, 8-5′-DFA and pCA esters [32]. Additionally, it was demonstrated that the DFAs in the pith of the basal section of the maize internode could facilitate MCB larval feeding inside the stem in particular synthetic varieties [28]. Nowadays, Santiago and coworkers has divided the research topic in two branches: evaluation of corn borer resistance in a divergent selection program for DFAs concentration, and study of the variation in the hydroxycinnamates contents after borer attack.…”
Section: Cell Wall Bound Hydroxycinnamatesmentioning
confidence: 99%
“…Barros-Rios and coworkers (2011) found that the stem tunneling by ECB and MCB was negatively correlated with total DFAs, 8-5′-DFA and pCA esters [32]. Additionally, it was demonstrated that the DFAs in the pith of the basal section of the maize internode could facilitate MCB larval feeding inside the stem in particular synthetic varieties [28]. Nowadays, Santiago and coworkers has divided the research topic in two branches: evaluation of corn borer resistance in a divergent selection program for DFAs concentration, and study of the variation in the hydroxycinnamates contents after borer attack.…”
Section: Cell Wall Bound Hydroxycinnamatesmentioning
confidence: 99%
“…Stalk strength is significantly positively correlated with the contents of cellulose, hemicellulose, and lignin [ 17 ]. Furthermore, corn borers significantly increase the rate of stalk lodging by drilling into stalks [ 18 ], whereas maize stem rot weakens stalk tissue, which greatly increases the risk of stalk lodging [ 19 ]. In additionally, the method of mounting specimens almost always has a significant effect on the measured mechanical response [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stalk strength is signi cantly positively correlated with the contents of cellulose, hemicellulose, and lignin [8,14]. Furthermore, corn borers signi cantly increase the rate of stalk lodging by drilling into stalks [15], whereas maize stem rot weakens stalk tissue, which greatly increases the risk of stalk lodging [16]. Moreover, as plant density increases, the length of the basal internode signi cantly increases and the diameter signi cantly decreases, the contents of cellulose, hemicellulose, and lignin, and the stalk mechanical strength decrease, and the risk of lodging increases [14].…”
Section: Introductionmentioning
confidence: 99%